Implementasi Penertiban Reklame yang Tidak Berizin di Kota Bandung - Ariq Alauddin; Abdul Rohman (UNISBA Press, 2022)
Abstract. In the State of Indonesia, since January 1, 2001, regional autonomy has been implemented. Regional autonomy is implemented based on Law Number 23 of 2014 as amended by Law Number 9 of 2015 concerning Regional Government, hereinafter referred to as the Regional Government Law. This means that the Regional Government is given the authority by the Act to manage and administer its own area. One way to increase and implement regional autonomy itself by the Bandung City Government focuses on increasing regional original income through the implementation of billboards. Advertisements based on the Regional Regulation of the City of Bandung Number 2 of 2007 concerning the Implementation of Advertisements. billboards are an inseparable part of the modern social system and society. The method used in this research is normative juridical, with a statutory approach and a case approach. With library research data collection techniques, this is done by collecting secondary data which includes primary legal materials, secondary legal materials, and tertiary legal materials. As well as the research specifications used are descriptive analytical. It was concluded that the Bandung City Government has made efforts to control the implementation of billboards that are not in accordance with the provisions for their placement, namely through mechanisms regarding licensing and supervision carried out by relevant agencies mandated by Bandung Mayor Regulation Number 217 of 2018 concerning Instructions for the Implementation of Billboards. Abstrak. Di Negara Indonesia, sejak tanggal 1 Januari 2001 telah memberlakukan otonomi daerah. Otonomi daerah dilaksanakan berdasarkan Undang-undang Nomor 23 Tahun 2014 sebagaimana telah diubah dengan Undang-undang Nomor 9 Tahun 2015 Tentang Pemerintahan Daerah, yang selanjutnya penulis sebut UU Pemda. Artinya Pemerintah Daerah diberikan wewenang oleh Undang-undang tersebut untuk mengelola dan mengurus daerahnya sendiri. Salah satu cara untuk meningkatkan dan melaksanakan otonomi daerah sendiri oleh Pemerintahan Kota Bandung menitikberatkan peningkatan pendapatan asli daerah yang melalui penyelenggaraan reklame. Reklame berdasarkan Peraturan Daerah Kota Bandung Nomor 2 Tahun 2007 Tentang Penyelenggaraan Reklame. reklame merupakan bagian yang tidak terpisahkan dari sistem dan sosial masyarakat modern. Adapun metode yang digunakan dalam penelitian ini yakni yuridis normatif, dengan pendekatan perundang-undangan dan pendekatan kasus. Dengan teknik pengumpulan data Studi Kepustakaan, ini dilakukan dengan cara mengumpulkan data sekunder yang meliputi bahan hukum primer, bahan hukum sekunder, dan bahan hukum tertier. Serta Spesifikasi Penelitian yang digunakan bersifat Deskriptif Analitis. Diperoleh simpulan bahwa Pemerintah Daerah Kota Bandung telah melakukan upaya dalam penertiban penyelenggaraan reklame yang tidak sesuai dengan ketentuan penempatannya adalah melalui mekanisme mengenai perizinan dan pengawasan yang dilakukan oleh dinas-dinas terkait yang dimandatkan oleh Peraturan Wali Kota Bandung Nomor 217 Tahun 2018 Tentang Petunjuk Pelaksanaan Penyelenggaraan Reklame.